(untitled) (Chemical Engineering Research Bulletin, 2026)
With the continuous increment in the world population, the demand for food products has also increased noticeably. To meet this huge demand, a stable supply of food products is required to be maintained strictly. For this reason, different chemical substances such as fertilizers and pesticides are used to aid food production. But arbitrary uses of pesticides will certainly lead to various environmental and health hazards. Hence, uses of pesticides are to be strictly monitored. Models to predict the residual fate of chemicals in plants can be effectively used in pesticide design, human exposure, and environmental assessments. Often the emissions of pesticides are non- steady due to changing plant growth and transpiration. A first principle model (FPM) has been built correlating different mass transfer modes in plants. For the modelling purposes, a material balance approach was used to set up ordinary differential equations (ODEs) for four compartments of the plants, namely, root, stem, fruits/crops, and leaves. The four ODEs were then simultaneously solved in MATLAB to estimate concentrations of pesticides in plant compartments with respect to time. Chlorpyrifos (CP) and Endosulfan Sulfate (ESS) are chosen as pesticides and wheat is selected as the plant for experiment. Concentration profiles were obtained for each pesticide using different input scenarios such as spraying the pesticide in air and applying the pesticide into soil. The model results can be used to find the pre-harvest time before which pesticides should be applied and by the time of harvest the pesticide concentration will fall below the safe threshold limit. Chemical Engineering Research Bulletin: 24 (Issue 1): 47-55